«LE POETIQUE HABITE DANS L’HOME » – COMMENTAIRES SUR HEIDEGGER - Manolescu, Gorun (European Scientific Journal, ESJ, 2014)
According to Heidegger there are some dangers threatening a rational thinking. But it seems to be others ways of knowledge and action beyond a rational thinking. Those are mystic and poetic modes. Heidegger said “poetically man dwells on the earth”. Paraphrasing Heidegger – and in fact following him – I state: "poetry lives in man". The two formulae express both an existential disappointment and a deep epistemological need. As we know, for the ordinary people poetry was and is a preceding form of knowledge and expression of sensitivity: precursory to the philosophical and scientific formalisation of knowledge. But for Heidegger: “The good and thus wholesome danger is the nighness of the singing poet./ The evil and thus keenest danger is thinking itself. It must think against itself, which it can only seldom do. “. Therefore Poetry is maybe better another way of access to the truth of being. Thus, it seems that the most important reason of poetry is its possibility to be an antidote of the danger represented by the philosophical thought itself. Is there an identity between poetry and mysticism? My text tries to offer an answer using a work of Derrida where Heidegger is opposed to Kant. Finally, I remark Heidegger’s philosophical-poetical discourse by which nothing is stated in an apodictic manner, but all is metaphorically suggested. It seems to be a third way of thinking that Heidegger not highlights but practice it.